Elucidating the daily foraging activity pattern of Oecophylla smaragdina to minimize bite nuisances in Asia large agro-system plantations - Exelis, Moïse Pierre; Ramli, Rosli; Abdul Latif, Samshul Amry; Idris, Azarae; Clemente-Orta, Gemma; Kermorvant, Claire (Elsevier, 2024)
Oecophylla smaragdina F., the Asian weaver ant, is one of the oil palm plantation’s (Elaeis gui neensis) potential predators, for the invasive bagworm species Metisa plana Walker, but this ant is a nuisance species that irritates plantation workers with their sharp bites. Here we assess the foraging activities (FA) of O. smaragdina’s major workers, identify its inactive times and the ex istence of supervision, a novelty for social insects. Between 2018 and 2022, the pattern of trunk foraging activity was used as a mitigation measure. The relationship between trunk FA and air temperature (AT), relative humidity (RH), air pressure (AP), and rainfall interception (RI) was also investigated. Our results showed that, O. smaragdina is a strictly diurnal ant species, has little to no crepuscular activity, and stopped foraging during darkness. Moreover, veteran bigger workers systematically acted as supervisors by monitoring trails, intercepting, and bringing back to nests smaller individuals during heat peaks. In relation to population size relative abundance, all colonies displayed greater intensity during the warmest daily periods with higher mean forager density among the bigger colony, regardless of the dry-rainy intervals corresponded to minimal activity from late scotophase to early photophase and showed a bimodal pattern. Thus, forager activity peaked between 1100–1530 h and 1745–1845 h, and an average two-fold daily sudden decrease in intensity between 1620 and 1650 h as a partial cut-off period (first report). Furthermore, foraging activity, AT, AP showed a significant positive correlation while RH was negative. Finally, we found that from the base palm trunks, defensive territorial layers extended to 5 m on average with different spatial configurations indicating greater foraging density within